Difference in Condom Use Between Bear Concordant and Discordant Dyads During the Last Anal Sex Event. Issue 2 (28th January 2017) - Schnarrs, Phillip W.; Rosenberger, Joshua G.; Schick, Vanessa; Delgado, Adolph; Briggs, Lindsay; Dodge, Brian; Reece, Michael
ABSTRACT: The purpose of this study was to understand how bear identity influenced condom use during the last anal sex event. Participants were recruited to complete an online, anonymous self-report survey through bear-related sexual and social networking websites. A total of 1, 080 men who identified as gay or bisexual and as a member of the bear community and were 18 years or older completed the survey. Overall, fewer than a third of men reported condom use during the most recent receptive (28%) and insertive (30%) anal sex event. Men in bear concordant pairings were less likely to use a condom during receptive and insertive anal sex compared to those is discordant pairings ( p  < .05). Findings suggest that bear identity concordance influences condom use during anal sex after accounting for an individual's relationship to their most recent partner as well as other confounding variables.